Preface - Arezes, P. (2019)
[Excerpt] Occupational and Environmental Safety and Health is a compilation of the most recent work of some selected authors from 14 countries within the domain of occupational safety and health (OSH). The included works are focused on selected topics, including occupational safety, risk assessment, safety management, ergo-nomics, management systems, environmental ergonomics, physical environments, construction safety and human factors, among others. This book represents the state of the art and it is mainly based on research carried out at universities and other research institutions, as well as some on-field inter-ventions and case studies. Due to the broad scope, relevance and originality of the contributions, it is expected that this book contains useful and up-to-date infor-mation, and it presents fundamentally scientific research that is being carried out in the subject, as well as it contributes to the outreach of practical tools and approaches currently used by OSH practitioners in a global context. All the included contri-butions were selected based on their potential to show the newest research and approaches, giving visibility to emerging issues and presenting new solutions in the field of occupational safety and health. [...]